Teater Melayu : suatu risalah pemikiran Melayu - Kamaluddin Abd. Rahman (Kuala Lumpur : Dewan Bahasa dan Pustaka, 2007)
History of various genres in Malay drama, 1870s-1960s reflecting sociocultural changes in Malaysia
Includes bibliographical references (p. 213-220) and index
In Malay
Keywords: Malay drama -- Malaysia -- History -- 19th century; Malay drama -- Malaysia -- History -- 20th century; Theaters -- Malaysia -- History -- 19th century; Theaters -- Malaysia -- History -- 20th century